A produção de periferias urbanas em uma cidade do agronegócio e fronteiriça: o bairro do Passo - São Borja (rs) - Nola Patrícia Gamalho (Confins)
The urban development processes of interior cities have progressively become important objects of study in geographic science. In this sense, this article seeks to reflect on the production of a neighborhood identified as a periphery in the context of a border city and agribusiness. The objective was, based on the concept of landscape (Verdum, 2012, Berque, 1998), narratives in semi-structured interviews and analysis of cartography, using aerial photographs from 1965, 1996 and a Google Maps image from 2015, to weave the neighborhood’s production processes and their fragmentations. It was possible to recognize their differences in villages, as well as otherness, physical and symbolic, resulting from inequality processes.